The Chesapeake and Ohio Railway, George Washington's railroad - Dorin, Patrick C. (Seattle, Wa. : Superior Pub. Co., 1981)
Examines the history, services, accommodations, and problems of the Chesapeake and Ohio Railway.
Includes index.
Bibliography: p.
Mode of access: Internet.
Keywords: Chesapeake and Ohio Railway Company -- History